Analysis of the ionosphere irregularities in E region based on COSMIC occultation data. Issue 9 (1st November 2015) - Niu, Jun; Fang, HanXian; Wang, Xi-xi; Weng, Libin; Guo, Lan
Abstract Sporadic-E layer is a usual phenomenon in ionosphere which has an important impact on the satellite navigation, communication, radar system and so on. In this paper, by using a wavelet decomposition and reconstruction technique, fluctuation of slant total electron content have been obtained which shows a strong enhancement at the Es layer altitude. The COSMIC data during year 2007 have been calculated by using this method; global distribution and seasonal variation both show well agreement with the Es layer feature which confirm the validity of the method. Linear and non-linear empirical formulas between TEC fluctuation and Es critical frequency are built and these formulas indicate that it may be better in inversing the strong Es.